Distal Femoral Replacement With a Metaphyseal Sleeve: Outcomes and Risk Factors for Subsidence - David Alexander George, MBChB, BMedSc, FRCS (Tr & Orth); Christopher Lee Buckle, MBBS, BSc, MSc (Oxon), FRCS (Tr & Orth); Abtin Alvand, BSc (Hons), MBBS, DPhil (PhD), FRCS (Tr & Orth); William Jackson, MBBS, BSc, FRCS (Tr & Orth); Adrian Taylor, MBBS, FRCS (Orth); Ben Kendrick, DPhil (PhD), FRCS (Tr & Orth) (Arthroplasty Today)
In this study, we report on the outcomes of our experience using a metaphyseal sleeve with a distal femoral replacement (DFR) and review the risk factors for sleeve subsidence over a 3 year period.